Dangerous sexualities : medico-moral politics in England since 1830 - Mort, Frank (Routledge, 2000)
This long-awaited new edition of Frank Mort's classic examines ideas of health and illness and their links to moral and immoral notions of sex, from 1830 to the present day. Includes new studies of eugenics, race hygiene and social imperialism.